A Pelatihan Implementasi Kurikulum Merdeka Jenjang Sekolah Dasar (SD) di Kabupaten Soppeng - Patang; Mustarin, Amirah; Subariyanto; Jamaluddin; Idris, Andi Puspa Sari (Jurusan Teknik Informatika dan Komputer, 2023)
This training aims to increase the knowledge and understanding of elementary school teachers in planning and implementing the Independent Curriculum in Soppeng Regency. This training was carried out offline and attended by 24 participants, consisting of six schools, 12 teachers, six principals, and six school supervisors. The training activities were held on June 27, 2023, at SMP Negeri 3 Soppeng Regency. Based on the results that have been obtained, the target school has implemented an independent curriculum for one year and has planned and implemented the independent curriculum well. In preparing the school's operational curriculum, the entire school community has been involved, consisting of all teachers and principals, parents of students, and student representatives. In the learning process in the classroom, differentiated learning has been implemented and is based on the achievements, characteristics, and needs of students.